Telehealth regulating together pilot trial: emotion regulation intervention for autistic children and adolescents - Coffman, Marika; Wells, Miranda; Schmitt, Lauren M.; Reisinger, Debra L.; Horn, Paul S.; Shaffer, Rebecca C. (Frontiers in Psychiatry, 2024)
Introduction: Autistic children and adolescents frequently experience emotion dysregulation, or difficulties with appropriately modifying their emotional reactions. Caregivers of autistic teens frequently seek psychotherapy support for navigating challenges associated with emotion dysregulation. During the COVID-19 pandemic, access to clinical services became limited, with interventions halted or transitioned into a telehealth format. Methods: This study evaluates the feasibility, acceptability, and initial efficacy of a telehealth adaptation to an existing intervention for emotion dysregulation for children and teens with autism, Regulating Together. A within-subjects trial was conducted for Child (ages 8-12) and Teen groups (ages 13-18). The trial consisted of a 5-week-control lead-in period, a 5-week-intervention, and 5-and 10-weeks-post-intervention follow-ups. Results: Twenty-eight youth with ASD + ED (n=13 Child and n=15 Teens, 71% male) participated. We observed a 93% retention rate across both groups. Improvements were found in reactivity, irritability, emotion and behavioral regulation, and flexibility immediately post-intervention and 10-weeks post-intervention in both groups. Additional improvements in dysphoria, cognitive regulation, and emotional control were observed in teens. Discussion: Our results suggest promising improvements in ED through telehealth delivery of an emotion regulation intervention in autistic children and adolescents, along with possible improvements in accessibility of this intervention.